Analysis on tool wear during milling carbon fiber reinforced polymer in dry, coolant and chilled air condition - Mustafa, Aisyah Madihah; Abd Halim, Nor Farah Huda; Tomadi, Siti Haryani; Shahruddin, Najlah Sakinah; Nasaruddin, Ricca Rahman (Malaysian Tribology Society (MYTRIBOS), 2023)
The demand of the Carbon Fiber Reinforced Polymer (CFRP) has been significantly increasing over the years especially in automotive and aerospace since CFRP possesses an excellent strength-to-weight ratio. However, milling CFRP challenging due to its anisotropic and heterogeneous property therefore produce brittle and dust-like chips. As CFRP is a combination of layers of carbon fibers embedded in matrix resin, machining process must be conducted below the glass transition temperature (Tg) of the matrix resin as it can degrade the CFRP. In this experimentto investigate the effect of cutting speed and cutting conditions on the tool wear during the milling process, CFRP was machined with 6mm diameter uncoated tungsten carbide tool with helix angle of 30°. Milling of CFRP was performed with three cutting speeds of 130, 150 and 170 m/min in three different cutting conditions which is dry, coolant and chilled air with constant feed rate of 2100 mm/min and depth of cut of 2 mm. The highest average tool wear of 110 μm was obtained during milling the CFRP with cutting speed 170 m/min in chilled air condition, 25.5% higher than the average wear of 82 μm at low cutting speed of 130 m/min in the same condition.